ApoB/ApoA-1 ratio and nitric oxide levels in pregnancy induced hypertensive women - Jammalamadaga, Visala Sree; Abraham, Philips; Sivaprasad, P. (International Journal of Research in Medical Sciences, 2016)
Background: Pregnancy induced hypertension is considered as the major cause of maternal and perinatal mortality. Even though occurrence of PIH is due to abnormal placentation, endothelial dysfunction plays a pivotal role in the genesis of the multisystem disorder that develops in pre eclampsia and eclampsia. Various studies have proved that hyperlipidemia is one of the major causes of endothelial dysfunction. Since ApoB/apoA-I ratio is a dyslipidemic indicator, the study was designed to determine ApoB/ApoA-I in PIH women and to analyse whether this ratio can be correlated with ED in PIH women. Methods: A cross-sectional analytical study involved normotensive, preeclamptic and eclamptic pregnant women with hundred subjects in each group. They were investigated for serum lipid profile, ApoA, ApoB, NO, MDA, FRAP in the 3rd trimester of pregnancy. Results: The SBP & DBP were significantly high between 3 groups. The mean plasma TC, TGL, VLDL, LDL, MDA, ApoB levels, ApoB/ApoA-I were significantly high & HDL, ApoA-I, NO, FRAP levels were significantly low between 3 groups. The ApoB/ApoA-I was positively correlated with TC, TGL, VLDL, LDL, malondialdehyde and negatively correlated with HDL, FRAP & NO. Conclusions: Our results indicate that women with PE & E exhibit markedly elevated concentrations of TGL-rich lipoproteins. The negative correlation between ApoB/ApoA-I with NO indicates that the hyperlipidemia is directly related with severity of ED in PIH. So, careful monitoring of ApoB/ApoA-I along with NO might be helpful to predict the onset and progression of the disease.